Role reversal of selected househusbands in Metro Manila - Ignacio, Klarizze Carmel M. (College of Home Economics, University of the Philippines Diliman, 2013)
This research was conducted with the aim to explore the role reversal experience of househusbands, to identify the usual reasons why husbands and wives reverse roles, to determine the perceived advantages and disadvantages of such role reversal, and to find out the effects of the role reversal on the marital satisfaction between spouses. A new family arrangement where wives work and husbands stay at home came about for practical reasons. The family's survival depends on the ability of family heads to find paid work; and at times, it is the female parent who must provide such support. This is not the traditional arrangement in Philippine society but it is becoming the trend in the urban areas. This exploratory study is an attempt to find how spouses manage the initial role switch until the full reversal of roles is attained and househusbandry becomes an accepted arrangement. Five middle-income couples from Metro Manila were selected as the unit of analysis. Tape recorded responses were transcribed, categories were drawn and verbatim responses were analyzed to facilitate interpretation of the results. Generally, husbands found the transition to househusbands fairly easy. Using the concepts of Biddle' role theory, role embracement and role reversal were processes that husbands went through without much hurdle because most of them were used to doing household chores. There was role strain due to additional housekeeping assignments, but there was only slight role confusion and no role conflict at all. Social pressure from family and friends were likewise minimal. They do get bored sometimes but still consider the current set up better than when they were working.